Optimizing Food Processing Efficiency: The Role of Forward Osmosis in Concentration - Julian, Helen; Lestari, Puji; Wenten, I Gede; Khoiruddin, K (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
This review comprehensively explores the application of Forward Osmosis technology in the food processing industry, focusing on its role in concentration processes. Amidst growing concerns over water scarcity, energy consumption, and environmental impact, Forward Osmosis emerges as a sustainable alternative to traditional methods, offering lower energy requirements and reduced environmental footprint. The paper delves into the theoretical foundations of Forward Osmosis, examining the osmotic process and the dynamics of semi-permeable membranes. It further investigates the technological implementations of Forward Osmosis in food processing, showcasing successful case studies and highlighting the technology performance advantages compared to other methods. Despite its potential, Forward Osmosis faces technical challenges, including membrane fouling and the need for efficient draw solution recovery mechanisms. Recent innovations in membrane and draw solution development are discussed, offering solutions to these hurdles and paving the way for more effective Forward Osmosis applications. The review also projects future directions and research needs to overcome existing limitations and fully harness Forward Osmosis capabilities. Through a critical analysis of current literature, this paper underscores Forward Osmosis transformative potential in making food processing more sustainable and efficient.